2018
DOI: 10.1093/gbe/evy184
|View full text |Cite
|
Sign up to set email alerts
|

Helena and BS: two travellers between the genera Drosophila and Zaprionus

Abstract: The frequency of horizontal transfers of transposable elements (HTTs) varies among the types of elements according to the transposition mode and the geographical and temporal overlap of the species involved in the transfer. The drosophilid species of the genus Zaprionus and those of the melanogaster, obscura, repleta, and virilis groups of the genus Drosophila investigated in this study shared space and time at some point in their evolutionary history. This is particularly true of the subgenus Zaprionus and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 80 publications
(127 reference statements)
1
5
0
Order By: Relevance
“…Our research group has been dedicated to the study of HTT between Zaprionus and the species of the subgroup melanogaster of Drosophila for a decade. The results reported in this study for the Jockey families agree with the hypothesis of recent transfer of retrotransposons with LTR (Gypsy, Micropia and Copia) [42, 43] and the non-LTR retrotransposons Helena and BS [9] between genomes of species of the subgenus Zaprionus and the subgroup melanogaster . Thus, the evidence we add here provides a consolidated picture of the extensive exchange of TEs between the species of these two groups in central Africa during the late Miocene.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Our research group has been dedicated to the study of HTT between Zaprionus and the species of the subgroup melanogaster of Drosophila for a decade. The results reported in this study for the Jockey families agree with the hypothesis of recent transfer of retrotransposons with LTR (Gypsy, Micropia and Copia) [42, 43] and the non-LTR retrotransposons Helena and BS [9] between genomes of species of the subgenus Zaprionus and the subgroup melanogaster . Thus, the evidence we add here provides a consolidated picture of the extensive exchange of TEs between the species of these two groups in central Africa during the late Miocene.…”
Section: Discussionsupporting
confidence: 89%
“…Studies have also shown that HTT occurs more frequently between closely related species than between more distantly related ones [4547]. Regarding the ecology and biology of the species involved in HTT, it has been shown that species with overlapping habitats share more TEs by HTT than species that are distributed in different environments [9, 42], as well as share more viruses that can be vectors of TEs [48]. Although susceptibility to viruses shows a strong phylogenetic correlation, susceptible hosts can occasionally be grouped into phylogenetically distant groups, allowing parasites to jump great phylogenetic distances [49].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among which, Drosophila melanogaster and Zaprionus indianus are the dominant species in the investigated orchard. These two Drosophilidae species that damage small fruit have invaded the Neotropics in recent decades (Valadão et al, 2019). The predominance of fruit flies in agroecosystems has been highlighted in African continent from their introduction into certain countries in and since that they had rapidly spread and established successfully across the continent (Mutamiswa et al, 2021).…”
Section: Discussionmentioning
confidence: 99%